CHANGES IN TORQUE-ANGLE PROFILES OF THE HAMSTRINGS AND HAMSTRINGS-TO-QUADRICEPS RATIO FOLLOWING TWO HAMSTRINGS STRENGTHENING EXERCISE INTERVENTIONS IN FEMALE HOCKEY PLAYERS. Issue 4 (1st February 2017) - Delextrat, Anne; Bateman, James; Jos, Vanrenterghem; Daniel, Cohen
Abstract : Background: Field hockey is characterised by high rates of hamstings strain injuries (HSI). While the Nordic Hamtrings (NH) is the most commonly used exercise in the prevention and rehabilitation of HSI, no study has investigated its isolated benefits compared to other well-established exercises in hockey players. Objective: To compare the effects of two hamstring strengthening interventions (nordic hamstrings (NH) vs. eccentric leg curl (ELC)) on the hamstrings torque-angle profiles and functional hamstrings-to-quadriceps ratio (Hecc :Qcon ) in female hockey players. Design: A randomised-control trials with repeated measures was used. Settings: The intervention for this study was used during practice sessions of university-level hockey players. Participants: Female university-level players were randomly allocated to a NH (n=9, age: 19.7±1.4 years; height: 168.4±4.4 cm; body mass: 66.2±7.2 kg), ELC (n=8, age: 19.5±1.0 years; height: 168.1±3.4 cm; body mass: 66.7±4.5 kg), and C (n=8, age: 19.6±1.4 years; height: 169.9±7.5 cm; body mass: 70.7±13.0 kg) groups. Main Outcome Measurements: Isokinetic concentric strength tests of the quadriceps (Qcon ), eccentric strength of the hamstrings (Hecc ) at 120°.s −1, and Hecc :Qcon. Interventions: Six-week intervention with ELC, NH or no (C) exercises performed three times weekly, before redoing the baseline strength assessments. Analyses of variance with repeated measures were used to assess the effects of angle, group and time on outcome measures. Results: Significant increases were observed in Hecc and Hecc :Qcon after the NH (+29.9% and +27.8%) and ELC (+30.5% and +38.3%) in the non-dominant leg only. Furthermore, significant shifts in the hamstrings eccentric APT towards a longer muscle length were shown in both legs (14.3 to 28.6%). Conclusions: These findings suggest that NH and ELC both resulted in significant improvements in peak and muscle length specific neuromuscular risk factors in the weaker limb, thereby reducing interlimb peak strength asymmetries.